TECHNOLOGY FOR IMPROVING INTERCULTURAL COMPETENCE IN STUDENTS - Sayyora Xamidova (European Science Publishing, 2025)
In the context of globalisation, the ability to effectively communicate and collaborate with representatives of different cultures – intercultural competence – is becoming a necessary quality for every individual, particularly for young professionals. This article examines the theoretical foundations and practical approaches based on modern pedagogical technologies for developing intercultural competence in students. The technology proposed in the article includes comprehensive methods aimed at forming intercultural knowledge, skills, attitudes, and awareness. The purpose of the study is to develop an effective technology for improving students' intercultural competence and to substantiate its significance in the educational process. The article analyses the components, stages, and expected outcomes of this technology.
Keywords: Intercultural training, linguistic tools, interactive technologies, and understanding linguistic tools.